Economic Evaluation of Dulaglutide vs Traditional Therapies: Implications of the Outcomes of the Rewind Study - Torre E; Bruno GM; Di Matteo S; Martinotti C; Valentino MC; Bottaro LC; Colombo GL (Dove Medical Press, 2020)
Enrico Torre,1 Giacomo M Bruno,2 Sergio Di Matteo,2 Chiara Martinotti,2 Maria Chiara Valentino,2 Luigi C Bottaro,3 Giorgio L Colombo4 1Endocrinology Diabetology and Metabolic Diseases Unit - ASL3, Genoa, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche S.r.l., Health Economics & Outcomes Research, Milan, Italy; 3General Direction, ASL3, Genoa, Italy; 4Department of Drug Sciences, School of Pharmacy, University of Pavia, Pavia, ItalyCorrespondence: Giorgio L ColomboDepartment of Drug Sciences, School of Pharmacy, University of Pavia, Pavia, ItalyEmail giorgio.colombo@unipv.itBackground: Diabetes represents a relevant public health problem worldwide due to its growing prevalence and socioeconomic burden, principally due to the development of macrovascular and microvascular complications as well as to the continuous launch of new and even more expensive drugs. The aim of our study is to evaluate the economic impact of dulaglutide, a weekly GLP-1 receptor agonist, on the treatment of diabetic patients as an alternative to both high dose sulphonylureas and insulin basalization at the failure of oral therapies alone. We carried out a cost-effectiveness analysis developed considering the economic implications of recent clinical studies regarding cardiovascular risk drug effects and especially of REWIND studies outcomes, focusing on the impact of weight changes on HRQoL.Material and Method: In our analysis, we have applied the cost-utility technique to the above reported clinical outcomes and compared the global costs of dulaglutide versus sulfonylurea or basal insulin, all in add-on with metformin. We have chosen gliclazide, as a sulfonylurea and Abasaglar®, the less expensive among basal insulin analogues. Abasaglar was titrated to 20 IU, corresponding to the mean dosage used in the treatment of type II diabetic patients. The model aims to estimate total direct costs related to the above-reported treatments and find out the real gap in costs between dulaglutide, the apparently cheaper gliclazide and basal insulin glargine (IGlargine) based on the Italian National Healthcare System (INHS).Results: The total cost of dulaglutide has resulted in € 859.66 higher than gliclazide (€ 1,579.73 vs € 720.07) and basal insulin, although less significantly, reporting a difference of € 396.54 (€ 1,579.73 vs 1,183.19). Except for the purchase cost, dulaglutide has reported reduced costs compared to insulin IGlargine and gliclazide. Dulaglutide showed lower self-monitoring blood glucose and hypoglycaemia costs, a significant reduction in costs related to cardiovascular complications, as well as savings in costs in other drugs. Dulaglutide can be considered a cost-effective antidiabetic therapy, due to the positive impact on the quality of life induced by weight reduction, despite the higher annual cost per patient, mainly influenced by drug purchase cost.Discussion and Conclusion: In this cost-utility analysis, dulaglutide has shown to be a cost-effective treatment option from the Italian healthcare system perspective as add-on therapy to metformin in patients with inadequately controlled type 2 diabetes mellitus. Study findings can provide stakeholders valuable evidence to support the adoption of this cost-effective second- or third-line therapy compared to gliclazide or basal insulin glargine. Dulaglutide cost-effectiveness has been particularly evident in the comparison with basal insulin glargine, indicating that, in patients who have treatment indication, this therapy may be preferred to basalization avoiding related complications and costs.Keywords: dulaglutide, cost utility analysis, diabetes type II